Study of Nanotechnology in Developed World - Nirala, Upendra; Patel, Mili; Singh, Prateek Kumar (International Journal For Research In Advanced Computer Science And Engineering, 2016)
Nanotechnology, despite its fantastic sounding name, is actually very practical for developing countries to make products better and cheaper. Technical innovations will increasingly shape developing economies and strengthen market robustness and build. This paper discusses the range of sciences currently covered by nanotechnology. It begins with a description of what nanotechnology is and how it relates to previous scientific advances. It then describes the most likely future development of different technologies in a variety of fields. The paper also reviews the government’s current nanotechnology policy and makes some.